Fragranced consumer products: effects on asthmatic Australians - Steinemann, A.; Wheeler, A.; Larcombe, Alexander (2018)
Exposure to fragranced consumer products, such as air fresheners and cleaning supplies, is associated with adverse health effects such as asthma attacks, breathing difficulties, and migraine headaches. This study investigated the prevalence and types of health problems associated with exposure to fragranced products among asthmatic Australians. Nationally representative cross-sectional data were obtained in June 2016 with an online survey of adult Australians (n = 1098), of which 28.5% were medically diagnosed with asthma or an asthma-like condition. Nationally, 55.6% of asthmatics, and 23.9% of non-asthmatics, report adverse health effects after exposure to fragranced products. Specifically, 24.0% of asthmatics report an asthma attack. Moreover, 18.2% of asthmatics lost workdays or a job in the past year due to fragranced products in the workplace. Over 20% of asthmatics are unable to access public places and restrooms that use air fresheners. Exposure to fragranced products is associated with health problems, some potentially serious, in an estimated 2.2 million asthmatic adult Australians. Asthmatics were proportionately more affected than non-asthmatics (prevalence odds ratio 3.98; 95% confidence interval 3.01–5.24). Most asthmatics would prefer workplaces, healthcare facilities, and environments that are fragrance-free, which could help reduce adverse effects.